Skills for practice in occupational therapy - Duncan, Edward A. S., ....-; Turner, Annie, ....- (Edinburgh : Churchill Livingstone, 2009)
This book is the companion volume to Duncan: Foundations for Practice in Occupational Therapy 5e and provides a comprehensive guide to the practice applications of the theory base. It is designed to be a 'basic and beyond' text, of value to students throughout their studies but also a valuable reference text to clinicians. The sections cover the following essential skills for effective occupational therapy practice: clinical skills, management and leadership skills, evidence-based and research skills, and thinking, judgement and decision-making skills.
Includes bibliographical references and index.
Keywords: Ergotherapie -- Praktijk; Occupational Therapy; Occupational therapy; Professional Competence